Previsões de inflação com a curva de Phillips - Jaguaribe, Felipe L. da S. (2007)
The object of this paper is to investigate the quality of inflation rates's forecasts utilizing an alternative approach in instead of the unemployment rate Phillips traditional curve one. We will use some variables that reflect the economic activity's levei in Brazil in substitution of the gap between the unemployment rate and the NonAccelerating Inflation Rate of Unemployment (NAIRU). These variables will be worked and classified among forecast errors leveis, considering some criterias mentioned in this paper. Then final result suggests some publicly available economic activity's indicators and variables that better interact with the brazilian inflation dynamic.